Educative attention to diversity. Deaf students in the classroom of Portugal and Turkey - Vicente J. Llorent García; María López González (Foro de Educación, 2010)
In this publication we intend to present some results of the innovative experience that we are realizing through Project SMILE. We have focused on the analysis of the relationships established around deaf students in schools and the role of sign language and its integration in the teaching-learning processes. This research is based on the perceptions of the authors of this article, teachers in schools where children are educated deaf children, hearing and deaf students, and university students who realized the practices on-site. Here we highlight the specific situation on the attention to diversity and equal opportunities, focusing on the situation of deaf learners in schools in Turkey and Portugal.